2014
DOI: 10.1021/cm404028f
|View full text |Cite
|
Sign up to set email alerts
|

Cation Gating and Relocation during the Highly Selective “Trapdoor” Adsorption of CO2 on Univalent Cation Forms of Zeolite Rho

Abstract: Adsorption of CO 2 and CH 4 has been measured on the Na-, K-, and Cs-forms of zeolite Rho (0−9 bar; 283−333 K). Although CH 4 is excluded, CO 2 is readily taken up, although the uptake at low pressures decreases strongly, in the order Na + > K + > Cs + . Structural studies by powder X-ray diffraction (PXRD) suggest that cations in intercage window sites block CH 4 adsorption; however, in the presence of CO 2 , the cations can move enough to permit adsorption (several angstroms). Determination of timeaveraged c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

15
158
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 106 publications
(173 citation statements)
references
References 29 publications
15
158
0
Order By: Relevance
“…22,23 The slow kinetics observed for the Na-rich end of the solid solution series can be attributed to the presence of Na + cations in 8R window sites at levels that require access to cages in the structure via occupied windows, with resulting need for cation movement. In situ synchrotron PXRD ( Figure S2.11, also Table S2 different from what is seen with Li-Rho.…”
Section: Adsorption On Mixed Cationmentioning
confidence: 99%
See 3 more Smart Citations
“…22,23 The slow kinetics observed for the Na-rich end of the solid solution series can be attributed to the presence of Na + cations in 8R window sites at levels that require access to cages in the structure via occupied windows, with resulting need for cation movement. In situ synchrotron PXRD ( Figure S2.11, also Table S2 different from what is seen with Li-Rho.…”
Section: Adsorption On Mixed Cationmentioning
confidence: 99%
“…[14][15][16] Recent computational studies have demonstrated that extraframework cations can move in the presence of CO 2 , 17 making cation gating effects possible. [18][19][20][21][22][23][24] In the postulated 'trapdoor' mechanism, cations occupying window sites permit the passage of molecules such as CO 2 or H 2 O that interact strongly with cations but block the windows to molecules that interact more weakly (such as CH 4 or N 2 ). These 'trapdoor' 3 zeolites adsorb CO 2 from mixtures of CH 4 or N 2 with very high selectivity.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Typically, moderate selectivity for CO 2 over N 2 or CH 4 can be achieved over cationic zeolites such as Na-X [4] or Na-A [5], which result from the quadrupole moment of CO 2 and its polarisability. Recently, however, small pore zeolites of specific structures and compositions have been found to show very high selectivity for CO 2 over less polar gases such as CH 4 and N 2 due to a molecular 'trapdoor' effect that makes them strong candidates as sorbents for carbon capture [6][7][8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%